PELAKSANAAN PEMBELAJARAN JARAK JAUH MASA PANDEMI (PENELITIAN DESKRIPTIF DI KELAS B TK IT INSAN MULIA) - Devy, Masta; Risina, Duana Fera (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2022)
The pandemic period has had a considerable impact on the lives of Indonesian people, one of which is the aspect of education. The government issued a policy regarding the implementation of learning to be carried out remotely or online, during the pandemic. This study aims to describe how the implementation of online distance learning during the pandemic in class B TKIT Insan Mulia. The research method used is descriptive qualitative method with interactive data analysis which includes 1) data collection, 2) data reduction, 3) data presentation, 4) conclusion drawing. The data collection techniques in this study used the techniques of 1) observation, 2) interviews, 3) documentation with data sources from teachers, students, parents, the implementation of distance learning during the pandemic in class B TKIT Insan Mulia took place online, using the WhatsApp application and zoom. The teacher carries out the learning process with the stages of planning, preparation, implementation, evaluation and the role of parents. The results of the study indicate that the process of implementing distance learning is online and uses existing media in the environment around the house. However, there are obstacles in its implementation, namely an unstable internet network.